Analysis of Pre-Service Teachers' Reflective Thinking Ability Profile on Earth Physics Lectures - Rosmiati Rosmiati; Liliasari Liliasari; Bayong Tjasyono; Taufik Ramlan Ramalis; Muhammad Satriawan (Universitas Muhammadiyah Makassar, 2020)
The purpose of this research is describe the reflective thinking profile of pre-service physics teacher students in Earth physics lectures about Ocean climate. This research was conducted in the physics education study program in one of the Higher Education Institutions in NTB Province, with a total of 25 respondents who had taken the Earth Physics course. The technique used in data collection is the analysis of the physics course syllabus and two essay tests about climate material that integrated with indicators of reflective thinking ability from Dewey's framework. Based on the analysis of the syllabus, it was found that the syllabus applied to the subject of earth physics had not been oriented to the provision of certain skills including reflective thinking skills. In addition, based on data analysis that the average value for question 1 is 18.75 and question number 2 is 16.75 where the maximum average score is on the understanding aspect of 31 for question number 1 while the minimum average score on critical reflection aspect is 7. It means that pre-service physics teacher students have very low reflective thinking abilities in Earth Physics lectures on ocean climate.Keywords: Reflective thinking skills, Earth Physics Syllabus, Earth Physics Lecture